Enhancement of Frequency Control for Stand-Alone Multi-Microgrids - Kavita Singh (182141) (2021)
This paper presents dual-stage fractional order PID controller to enhance the primary frequency regulation of interconnected multi- μ grids in standalone mode. A rational, non-integer ordered calculus-based controller is assessed via a single-area microgrid system pursued by a two-area microgrid to integrate a tidal power plant (TPP). Additionally, it is employed with conventional units in frequency control to certify system steadiness. Thus, a strategy to showcase the contribution of TPP in frequency regulation with the integration of the diesel engine power plant is proposed. Also, the proposed methodology shows the support of TPP in primary frequency regulation strategies such as inertia, damping control, and supplementary control with deloading activity. For getting superior outcomes and enhanced steadiness of the microgrid, the controller gains are streamlined utilizing an imperialist competitive algorithm (ICA). To demonstrate the efficiency of ICA, The obtained results are compared with the genetic algorithm and particle swarm optimization algorithm. The proposed investigation is conducted in single-area and two-area microgrid systems through MATLAB simulation verification. The obtained results prove the effectiveness of the proposed methodology. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2021.3083960